Placing Teachers? Sustaining Rural Schooling Through Place-Consciousness in Teacher Education - Simone White; Jo-Anne Reid (Journal of Research in Rural Education, 2008)
This paper explores two seemingly disparate areas of social inquiry: teacher education and the sustainability of rural communities in Australia. It suggests that these may be usefully understood in close connection with each other, and that healthy rural communities may be supported via reform of the ways in which teacher education prepares graduates for teaching in rural schools. In making this argument we claim that consideration and consciousness of place are important for all teacher education curricula, not merely that on offer in rural and regional centers. We call for metropolitan-based teacher education institutions to consider curriculum practices that take a more active role in fostering healthy and productive rural communities through place-conscious approaches to pedagogy (Gruenewald, 2003). At the center of this call is a concern to ensure the provision of high-quality education for children in rural families and the need for well-trained teachers who are personally and professionally equipped to address the educational needs of their communities.